Influence of fiber treatment on dimensional stabilities of rattan waste composite boards - Ahmad, Zuraida; Y., Insyirah; Tajuddin, Maisarah; Halim, Zahurin (IOP Publishing Ltd., 2018)
The main drawback of using natural fibers in composite boards is its hydrophilic properties which absorb a high volume of moisture. This results in low dimensional stability of the produced composite boards. Hence, the purpose of this study is to investigate the effects of fibers’ treatment processes of the rattan waste fibers on the dimensional stabilities of composite boards. The collected fibers underwent two types of retting processes, namely a water treatment and alkaline treatment retting processes; where the fibers were soaked in water and a 1% sodium hydroxide (NaOH) solution, respectively. The fibers were dried and mixed with poly(lactic) acid (PLA) pellets with ratio of 30% fibers: 70% matrix; before being fabricated into composite boards via a hot-pressing process and were labelled as RF/PLA, WRF/PLA, CRF/PLA for untreated rattan, rattan treated by water retting, rattan treated by chemical retting, respectively. The produced composite boards were cut and soaked in water for 24 hours for dimensional stability in terms of water absorption and thickness swelling tests. The results showed that WRF/PLA has the lowest water absorption (3.2%), and the CRF/PLA had the highest water absorption (23.2%). The thickness swelling showed a similar trend as water absorption. The presence of void contents and fibers damaged the insides of the boards, which contributed to low dimensional stabilities of the composite boards. It can be concluded that water retting facilitated in improving dimensional stability of the produced composite board.